Scratching where it itches in the autobiographies of Harriet Jacob's incidents in the life of a slave girl and Bhanu Kapil's Schizophrene - Thango, Linda Thokozile (My University, 2017)
Set within a revisionist and feminist context, this thesis seeks to draw parallels in the autobiographical texts of Harriet Jacobs’ Incidents in the Life of a Slave Girl (1861) written by an African American ex-enslaved and Schizophrene (2011) penned by Bhanu Kapil, a British born Asian American, a descendant of a generation that live (d) through/with ‘what happened in a particular country on a particular day in August 14th 1947’ (Quaid). These literary representations will constitute the corpus of this research paper as it attempts to examine how these autobiographies draw attention to and break the notion of prevailing dominant geographies of oppression. In both texts, the authors juxtapose appropriation and hegemony with an alternative literary geographic narrative that seeks to recuperate the liminal (black) body and psyche. This research paper will seek to explore the multiple and interrelated ways in which both authors employ certain strategic mechanisms to re-appropriate tools of social power, thus exposing the frailties of their respective oppressive histories by disrupting their continued, albeit imagined stronghold on them. In employing their autobiographies as anthropological arsenals, these authors seem to demonstrate the manner in which history has attempted through its numerous sites of oppression not only to construct black victims and mere black bodies but also to un-write and evacuate its untidiness. These autobiographies will be employed to reconstruct and re-imagine the authors but symbolically the collective black body as more than objects but rather as humans with subjectivities and self-assertion. The paper further seeks to understand how these autobiographies tend to a vicious past of slavery and partition and how they translate these memories, remembering the depth of their experiences whilst also being haunted by their contemporary echoes. An accent will be given to the ambivalence, perversions and anxieties of these autobiographies.
A research report submitted to the Faculty of Humanities, University of the Witwatersrand in partial fulfilment of the requirements for the degree of Master of Arts, Johannesburg, 2017
Keywords: Jacobs, Harriet A.--(Harriet Ann)--1813-1897; Kapil, Bhanu--1968-; Slaves--United States--Biography; Women slaves--United States--Biography; Slaves--United States--Social conditions; Slavery--United States; African Americans--Biography; Asian Americans--Biography